Juvenile pleomorphic adenoma of the cheek: Report of a rare case and literature analysis. Issue 3 (December 2020) - Görürgöz, Cansu; Erdem, Murat Kaan; Erdem, Erdal; Gültekin, Sibel Elif
Abstract: Purpose: The aim of this paper is to describe a rare case of children with pleomorphic adenoma in buccal minor salivary gland and present a brief review of the previous cases in the literature. Methods: Research was conducted in the PubMed/MEDLINE/Google Scholar databases. The research was supplemented with a manual search to identify related published articles in dental journals. Results: Articles published from 1986 onwards, in English language with full texts, were selected. Our search revealed that only 6 cases of children with pleomorphic adenoma in cheek (including pleomorphic adenoma arising from accessory parotid gland) were reported in the last 34 years. This paper also reports a case of pleomorphic adenoma on the cheek in a 10-year-old girl. The mass diagnosed with Ultrasonography was removed by wide local excision and no recurrence has been noted with a follow-up period of 14 months. Conclusion: Salivary glands tumors are very rare in the pediatric age group, and rarely in minor salivary glands. Proper examination and assessment with preoperative imaging are necessary for its diagnosis. Pleomorphic adenoma should be included in the differential diagnosis of cheek lesions in young and adult patients. The possibility of late recurrences and malignant transformation should be regarded, thus prolonged follow-up is essential.